The Potentialities of Local Innovation Ecosystems to Tackle Wicked Problems: The Case of Aging - Albuquerque, Cristina P.; da Luz, Helena R. A. (Technology Transfer and Entrepreneurship (Discontinued), 2018)
The authors present, in the article, a critical approach about the characteristics and dimensions of wicked problems and discuss the application of this theoretical framework to the comprehension and action in a contemporary major issue: active and healthy aging. Under this conception, active and healthy aging promotion is conceived as a complex, uncertain and multidimensional problem requiring innovative forms of thought and intervention, namely in local or regional contexts. Innovative local ecosystems, engaging multiple stakeholders in a quadruple helix perspective, are presented as an adequate way to intervene in wicked problems’ response and particularly on the aging issues. At the end of the article, the authors present an example of a regional innovation ecosystem, in Portugal, associated with a global and synergic intervention in the domain of active and healthy aging and reflect on the critical elements of model’s replication.
Keywords: local ecosystem